Implementasi Kurikulum 2013 Guru Pendidikan Agama Islam di SMP Muhammadiyah 4 Kota Medan - Neliwati; Anisah Aruan; Afiq Faeyza; Futhri Raudhatul Kabry (Jurnal Ilmiah Edukatif, 2023)
Implementation of the 2013 curriculum is the application or implementation of a curriculum program that has been developed in the previous stage, then tested with implementation and management that is adapted to the situation and conditions in the field and the characteristics of students, including intellectual, emotional and physical development. The aim of the 2013 curriculum is to make learning more meaningful and useful for students, not just focusing on memorization and theory. The curriculum also focuses on developing students' overall learning abilities, including attitudes and physical skills. This research uses qualitative research methods, by conducting observations before the research, and collecting data based on the results of interviews with PAI teachers at SMP 4 Muhammadiyah Medan. Based on the results of researchers' observations regarding the implementation of the 2013 curriculum, PAI teachers at SMP Muhammadiyah 4 Medan, Medan Helvetia sub-district, Medan city still find it difficult to implement the 2013 curriculum, especially in the application of learning, apart from that, teachers feel burdened because they are required to understand the 2013 curriculum.